PENGEMBANGAN MODUL PERMAINAN TRADISIONAL GUNA MENUMBUHKAN KARAKTER TOLERAN ANAK USIA 6-8 TAHUN - Benedicta Rani Nugraheni; Gregorius Ari Nugrahanta; Irine Kurniastuti (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
This study aimed to develop a traditional game module, to determine the effectiveness of the use of traditional games to foster a tolerant character and to find out the quality of traditional game modules for children aged 6-8 years old. The method used in this research was research and development (R&D). This study involved five teachers in each district in Yogyakarta for gaining the needs analysis, four experts for expert judgment, and six children for limited experiment. The results showed: 1) The module was developed using ADDIE steps. 2) The quality of the module obtained a score of 3.43 which was included in the qualification of "Very Good" with the recommendation "No Need for Revision". The result of the face validity test was "Very good" with a score of 3.33. The results of the content validity test showed that the quality of the module was "Very Good" with a score of 3.5. 3) The application of traditional game modules affected the tolerant character of children. The t-test result of the posttest sample (M = 0.8667, SE = 0.04944) was higher than that of the pretest (M = 0.6500, SE = 0.08466). This difference showed the value of t (5) = 3.313, p = 0.021 (p <0.05). The amount of influence was r = 0.0637 which was included in the category of big influence with a percentage of 68.7%. The level of effectiveness was indicated by the N-gain score of 67.46% with the effectiveness category "Medium".